Endovascular Management of Deep Venous Thrombosis in Cancer Patients - Dongmo, Gauthier; Pal, Koustav; Sheth, Rahul A. (Seminars in Interventional Radiology, 2025)
Venous thromboembolism (VTE) remains a significant cause of morbidity and mortality in cancer patients. Although anticoagulation is the mainstay therapy, select patients may benefit from interventional radiology (IR)-guided procedures to address acute, chronic, or refractory thrombotic disease. This article outlines a comprehensive approach to managing cancer-associated VTE using a wide array of IR techniques, including inferior vena cava (IVC) filter placement, catheter-directed thrombolysis, and mechanical thrombectomy for deep venous thrombosis, pulmonary embolism, portal vein thrombosis, and tumor thrombus.
Keywords: venous thrombus; pulmonary embolism; cancer; malignancy; interventional radiology; thrombolysis; thrombectomy